2018
DOI: 10.1111/acer.13920
|View full text |Cite
|
Sign up to set email alerts
|

Acute Alcohol Intoxication Inhibits Bystander Intervention Behavior for Sexual Aggression Among Men with High Intent to Help

Abstract: Background: Bystander training programs aim to encourage third-party witnesses to intervene in high-risk sexual situations; however, these programs rarely focus on training bystanders to effectively intervene when intoxicated. This is not surprising due to the limited evidence on the proximal effects of alcohol on bystander intervention for sexual aggression. To this end, the aim of the present study was to test the effects of men's self-reported intent to help strangers and acute alcohol intoxication on the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 57 publications
4
40
1
Order By: Relevance
“…It is plausible that this difference is because the present study measured prior bystander behavior whereas related studies measured bystander attitudes or intentions. Notably, recent work suggests that alcohol alone may not deter bystander intervention; rather, alcohol may be particularly likely to inhibit intervention behavior as a function of relevant individual characteristics (Leone & Parrott, 2019b).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is plausible that this difference is because the present study measured prior bystander behavior whereas related studies measured bystander attitudes or intentions. Notably, recent work suggests that alcohol alone may not deter bystander intervention; rather, alcohol may be particularly likely to inhibit intervention behavior as a function of relevant individual characteristics (Leone & Parrott, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…The present study was drawn from a larger two-session laboratory-based study on acute alcohol intoxication and bystander intervention (Leone & Parrott, 2019b). Thus, all participants who presented to the laboratory reported that they had consumed alcohol during the past year (see below).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations